Recent Progress in Controlled Nanostructure of Colloidal Nanocrystal Powders for Efficient Light Emission - Naoto Shirahata (KONA Powder and Particle Journal, 2022)
The application of semiconductor nanocrystals containing cadmium, lead, selenium and mercury as constituent elements is strictly limited by concerns about environmental pollution and health effects. Nanocrystals free of these toxic elements are being pushed to the forefront of nanocrystal research because of their environmentally friendly advantages and attractive photophysical properties on recent advances in colloidal synthesis, excellent optical properties, optoelectronic device applications, and biological applications of these environmentally friendly fluorescent nanocrystals. In this context, the first topic in this review paper introduces group IV semiconductors. In particular, the unique light emitting properties generated in silicon nanocrystals of diameters smaller than bulk exciton Bohr radius are highlighted. Next the topic turns to the nanocrystals of group III–V semiconductors. After that, attentions are paid to the lead-free perovskite nanocrystals such as tin-based halide perovskite and double perovskite structures. Recent efforts on how to control nanostructures to enhance photoluminescence quantum yields is highlighted for each semiconductor nanocrystal. Finally, the remaining challenges that must be overcome to realize nontoxic optoelectronic devices will be discussed.